Electromyography: applied in the phonoaudiology clinic - Miriam Nagae; Fausto Berzin (Universidade Estadual de Campinas, 2015)
The aim of this study was to discuss the utilization of surface electromyography in the practice of phonoaudiology to obtain a picture of the muscular compromise that occurs in patients with dental and skeletal alterations. The behavior of muscles in functions such as swallowing, chewing and respiration, and at rest, and possible deviations thereof, will be examined by electromyography based on the activated muscular chains. Compromises such as tension, flaccidity, palsy and rhythm could be detected quantitatively and qualitatively during the functions.